2021
DOI: 10.1007/s40266-021-00913-y
|View full text |Cite
|
Sign up to set email alerts
|

Medical Cannabis Use Among Older Adults in Canada: Self-Reported Data on Types and Amount Used, and Perceived Effects

Abstract: Background Medical cannabis use is growing among older adults. In this retrospective study, we aimed to assess the characteristics of older medical cannabis users including the indications, type and amount of cannabis used, perceived changes in symptoms after cannabis use, change in dose of concurrent medications, and adverse effects. Methods Data were collected between October 2014 and October 2020 from patients who were consulting the Canada-wide network of clinics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 42 publications
9
15
0
Order By: Relevance
“…Nevertheless, our results showed that most participants, especially females, initiated their treatment with a CBD-predominant product containing <2 mg/mL of THC. This is in strong agreement with (i) a recent observational study including 9,766 Canadian older adults receiving treatment with medicinal cannabis in which 83.6% were receiving CBMPs containing only or mostly CBD ( 30 ); and (ii) the recommendations by an industry-sponsored multidisciplinary group of global experts who recently developed a set of clinical guidelines for the dosing and administration of cannabinoids to treat chronic pain through a modified Delphi process ( 26 ).…”
Section: Discussionsupporting
confidence: 84%
“…Nevertheless, our results showed that most participants, especially females, initiated their treatment with a CBD-predominant product containing <2 mg/mL of THC. This is in strong agreement with (i) a recent observational study including 9,766 Canadian older adults receiving treatment with medicinal cannabis in which 83.6% were receiving CBMPs containing only or mostly CBD ( 30 ); and (ii) the recommendations by an industry-sponsored multidisciplinary group of global experts who recently developed a set of clinical guidelines for the dosing and administration of cannabinoids to treat chronic pain through a modified Delphi process ( 26 ).…”
Section: Discussionsupporting
confidence: 84%
“…It appears that patients who participate in the medical access program increasingly are using cannabis oils instead of dried cannabis. This accords with the results of surveys of individuals who report using cannabis for medical reasons [31][32][33]. Most varieties of cannabis oil sold by Licensed Producers are now high in CBD and low in THC.…”
Section: Plos Onesupporting
confidence: 82%
“…More recent US surveys support this finding: more than 75% of adults over 50 who consumed cannabis in the past year had used continuously for at least three years, while less than 6% had initiated use for the first time in the past year [4]. Recent data suggest 6-7% of older adults use cannabis, and amongst them approximately 75% use it for medical purposes [5]. Older adults generally suffer from more chronic health conditions than younger adults (e.g., chronic pain, insomnia) [6,7] and, thus, may be attracted to cannabis for medical purposes [3,8] by marketing efforts that exaggerate the medical and "wellness" benefits of cannabis, while minimizing its harms [9], and by word-of-mouth anecdotal "evidence."…”
Section: Introductionmentioning
confidence: 94%